Micro-minerals content in feedstuff, blood and hair of camels maintained in irrigated north-western plain of arid zone of Rajasthan - SAINI, N; KIRADOO, B D; BOHRA, D L (The Indian Journal of Animal Sciences, 2014)
Micro-mineral profiles of feed and fodder, blood serum and hair of camels in 2 villages each from 2 Tehsils of Hanumangarh and Ganganagar districts of irrigated North-Western plain of arid Rajasthan were studied. The most of dry and green roughages and tree leaves were found deficient in Zinc. Crop residues contained copper at marginal level whereas tree leaves, green fodders and protein rich concentrate guar churi were found good source of Cu. Mn level in all feed stuffs were found adequate. Crop residues generally fed to camel contained adequate amount of Mn to meet requirement of camels. The all feed ingredients contained iron concentration in excess of requirement. Serum concentration of all trace minerals were within normal range. The blood serum Cu, Zn, Mn and Fe were well above than critical levels. The mean values of Zn observed in hair were lower than the normal values indicated inadequacy of its dietary supply. Mn in all hair samples was much higher than critical level <4.0 ppm. Cu level in hair was also marginal. Similar to feed and fodders and serum, iron concentration in hair was also much more than the normal minimum values. The study indicated that there is need of dietary supplementation of deficient minerals as area-specific mineral mixture for improving the productive and reproductive efficiency of camels of this region.